Towards inclusive food systems: Pandemics, vulnerable groups, and the role of social protection - Kumar, Neha (2021)
Neha Kumar GLOBAL FOOD POLICY REPORT GLOBAL LAUNCH EVENT - 2021 Global Food Policy Report: Transforming Food Systems After COVID-19 APR 13, 2021 - 09:30 AM TO 11:00 AM EDT